2019
DOI: 10.3390/ijms20194753
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Genetic Factors Associated with Resistance to Treatment in Patients with Schizophrenia: A Case-Control Study

Abstract: Objectives: To assess clinical and genetic factors affecting response to treatment in a sample of patients with schizophrenia (treatment-resistant patients versus treatment responders). We also aimed at examining if these factors are different when we consider two different resistance classifications (the positive and negative syndrome scale, PANSS and the brief psychiatric rating scale, BPRS). Material and Methods: A case-control study included treatment-resistant patients and good responders. Patients were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 64 publications
2
11
0
Order By: Relevance
“…Regarding COMT gene, several studies have suggested that this gene could be related to treatmentrefractoriness or responsiveness to medications, and most of those studies demonstrated that Met-allele carriers could be linked to treatment-refractoriness [Inada et al, 2003;Sagud et al, 2018;Hajj et al, 2019] with the exception of one report [Terzić et al, 2016], which was in line with our present nding. However, some research groups examining COMT and GAD1 suggested that the interacting effects of both genes could not simply explain the synthesis of GABA and the clinical phenotypes in schizophrenia.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding COMT gene, several studies have suggested that this gene could be related to treatmentrefractoriness or responsiveness to medications, and most of those studies demonstrated that Met-allele carriers could be linked to treatment-refractoriness [Inada et al, 2003;Sagud et al, 2018;Hajj et al, 2019] with the exception of one report [Terzić et al, 2016], which was in line with our present nding. However, some research groups examining COMT and GAD1 suggested that the interacting effects of both genes could not simply explain the synthesis of GABA and the clinical phenotypes in schizophrenia.…”
Section: Discussionsupporting
confidence: 91%
“…It has also been hypothesized that patients with TR may share genetic underpinnings (Nucifora et al, 2019). This is further supported by findings showing that family members of patients with TR are more likely to have a diagnosis of schizophrenia in comparison with family members of responsive patients with schizophrenia (Hajj et al, 2019;Silverman et al, 1987), indicating a common genetic component (Joober et al, 2005). Taken together, these findings indicate that TR might be at least partly determined by the burden of genetic risk for schizophrenia.…”
Section: Introductionmentioning
confidence: 84%
“…It might also be due to shared risk of genetic markers, environmental exposures or a combination of these factors with family history of mental illness ( 32 ). Previous studies have also shown that family history of mental illness have biological/hereditary effects and that other psychiatric problems in the family could indicate similar etiological factors in the development of the problems ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%